L’ histoire du Séminaire de Philologie Gréco-Latine à l’Université de Debrecen de 1914-1949 - Mudrák, József (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
No abstract is available for this article, published in Acta Classica Universitatis Scientiarum Debreceniensis, Issue XLII, 2006. At the time of publication, abstracts were not required from the authors. Please consult the full text for further details.